Influência da maturidade da planta de diferentes híbridos de milho no rendimento e na qualidade nutricional da silagem de espiga (“Earlage”) - Pajanoti, Ane Elise Gonçalves (2018)
The objective was to evaluate the yield and the bromatological composition of grain, cob, husk and earlage in different corn hybrids and maturity levels of the plant in the first experiment. Twelve cultivars of corn were planted in a randomized block design, with four repetitions. The treatments were arranged in a factorial scheme 12 x 4, being twelve hybrids and four moisture levels: 40, 35, 30 and 25%. Within each block, the harvest was made manually for high-moisture corn grain and earlage (40%; 35%; 30% and 25% moisture). The dry matter yield of the 12 maize cultivars ranged from 9354.40 and 11274.66 kg/ha. The three hybrids that stood out for the productivity in kg / ha dry matter of the earlage were: MG 580 PW, SYN5T78 VIP3 and MG 652 PW. Hybrids MG580 PW and SYN5T78 VIP3 obtained greater participation of grains in their composition. There was no difference in the production of cob among the hybrids (P> 0.05). With regard to production of husk, was observed the MG580 PW presented lower participation of this component in its composition. There was an effect of the chosen hybrid (P <0.05) on PB variables of earlage and grain. For the NDF content of cob and husk the linear effect (P <0.01) was verified, but for grain NDF the behavior was quadratic (P <0.01). It is recommended to produce the earlage when the moisture content is between 35 to 40%.The second experiment was carried out to evaluate the yield and the bromatological composition maize hybrids for the production of two types of silage: earlage and highmoisture corn grain. The treatments were arranged in a factorial scheme 12 x 2, being twelve hybrids and two forms of silage production. Hybrids were harvested with 35% moisture for ensiling. The experimental silos used were PVC pipes with 10 cm diameter and 50 cm length. DM contents of wet high-moisture corn grain silage ranged from 57.75 to 65.75. The influence of the hybrids and the types of silage evaluated for the ammoniacal nitrogen variable (P <0.05) was verified. There was a difference (P <0.05) in the pH content among the silages, except for cultivars DKB 390 PRO2 and 2A401 PW. The CP values of the earlage varied between 6.50 and 7.75%. There was a difference (P <0.05) between the type of silage for the variables ADF and NDF. For the analysis of non-fibrous carbohydrates, there was a difference between the type of silage studied (P <0.05). The increase in the proportion of corn and husk causes reduction of DM, CP, CNF and NDF contents of the earlage silage.